2022
DOI: 10.1038/s41586-022-05389-3
|View full text |Cite|
|
Sign up to set email alerts
|

Hydroclimatic vulnerability of peat carbon in the central Congo Basin

Abstract: The forested swamps of the central Congo Basin store approximately 30 billion metric tonnes of carbon in peat1,2. Little is known about the vulnerability of these carbon stocks. Here we investigate this vulnerability using peat cores from a large interfluvial basin in the Republic of the Congo and palaeoenvironmental methods. We find that peat accumulation began at least at 17,500 calibrated years before present (cal. yr bp; taken as ad 1950). Our data show that the peat that accumulated between around 7,500 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
30
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 89 publications
4
30
1
Order By: Relevance
“…There was clearly a strong association during the study period between C loss, subsidence and droughts driven by regional climate extremes 26 . Our results indicate that even low-level or indirect human disturbance (for example, by means of climate change) can lead to C loss, highlighting the hydroclimatic vulnerability of C in forested tropical peatlands [13][14][15][16] .…”
Section: Articlementioning
confidence: 73%
See 2 more Smart Citations
“…There was clearly a strong association during the study period between C loss, subsidence and droughts driven by regional climate extremes 26 . Our results indicate that even low-level or indirect human disturbance (for example, by means of climate change) can lead to C loss, highlighting the hydroclimatic vulnerability of C in forested tropical peatlands [13][14][15][16] .…”
Section: Articlementioning
confidence: 73%
“…Tropical peatlands cycle and store large amounts of carbon in their soil and biomass [1][2][3][4][5] . Climate and land-use change alters greenhouse gas (GHG) fluxes of tropical peatlands, but the magnitude of these changes remains highly uncertain [6][7][8][9][10][11][12][13][14][15][16][17][18][19] . Here we measure net ecosystem exchanges of carbon dioxide, methane and soil nitrous oxide fluxes between October 2016 and May 2022 from Acacia crassicarpa plantation, degraded forest and intact forest within the same peat landscape, representing land-cover-change trajectories in Sumatra, Indonesia.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In high northern latitudes wetlands, it has been shown that permafrost degradation leads to wetland shrinkage (Avis et al, 2011). In the tropics the situation is also critical, with anthropogenic (Moore et al, 2013) and natural (Schefuß et al, 2016;Garcin et al, 2022) factors contributing to the remobilization of pre-aged C from peatlands. Therefore, the release of large amounts of peat-derived OM described here for deglacial Europe has analogues in the present day and may be useful to inform future projections of permafrost peatland loss (e.g., Fewster et al, 2022), with our results advocating for the importance of better constraining the C cycle in wetlands.…”
Section: Landscape Development and Om Remobilization Mechanismsmentioning
confidence: 99%
“…The main threat climate change poses to peatlands comes from the increased duration or greater severity of drought, which drives rapid degradation of peat through oxidation, or increased likelihood of fire events (Loisel et al, 2020). This can result in substantial peat carbon loss, or prolonged periods when peat is not accumulating, as evidenced in the Central African peatland complex (Garcin et al, 2022). Under most future climate change scenarios, there will be strong increases in rainfall seasonality and intensity (IPCC, 2013;Li et al, 2007), but precise effects on peatlands will differ between regions.…”
Section: Climate Changementioning
confidence: 99%